ANALISIS KEAMANAN SITUS PRESTASI MAHASISWA UPNVJ MENGGUNAKAN METODE NIST SP 800-115 DENGAN KERENTANAN BERDASARKAN OWASP Top 10 - Rafael Salomo Sahat Piero, (2024)
Information technology is an inseparable part of human life at this time. One form of information technology that is widely used is websites. The website can be accessed from all devices that have internet and web browsers. Some websites provide services that require users to store and enter personal data such as addresses, identity numbers, credentials, and account numbers and there is also data generated from user activities while accessing the website such as transaction history. BSSN found 714,170,967 traffic anomalies or cyberattacks of which 272,962,734 occurred in January 2022 with 30% of attacks targeting academic institutions. Hackers or attackers are constantly finding new ways of carrying out attacks on applications. As the ability of hackers to penetrate web security systems develops, web security systems must be tested to find out the possibility of security loopholes that are missed by the developer. To carry out the security test, this study conducted penetration testing using the NIST SP 800-115 method with vulnerabilities based on the Top 10 OWASP on the UPNVJ prospective new student re-registration site. It is hoped that from the research, researchers will be able to find out and describe the vulnerabilities found on the UPNVJ New Student Candidate Re-list website along with recommendations for handlers and vulnerability levels.